2018
DOI: 10.1016/j.artd.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cost and determinants of acute kidney injury after elective primary total joint arthroplasty

Abstract: BackgroundAcute kidney injury (AKI) is a serious complication after major surgery, which may lead to increased morbidity and mortality. The aim of this study was to identify cost and determinants of AKI after total joint arthroplasty.MethodsA retrospective case-controlled study was conducted with 1719 primary elective total hip or knee replacements performed from January 2004 through September 2015 at an urban teaching hospital. Patients who developed AKI were matched in a 1:3 ratio with those in a control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Reported risk factors for AKI in patients undergoing THA are demonstrated in Table 2 [18,19,20,22,23,24,26,27,29,30,31,32,33,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. Older age [23,24,26,29,31,55,60], higher body mass index (BMI) [19,22,23,24,26,30,31,46,47,48,49,56,57,59], reduced baseline estimated glomerular filtration rate (eGFR)/chronic kidney disease (CKD) [31,54,55,57,60], diabetes mellitus (DM) [24,26,31,34,47,55,57], nonsteroidal anti-inflammatory drug (NSAID) [23,32,53] use, and perioperative blood transfusion [23,47,53,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported risk factors for AKI in patients undergoing THA are demonstrated in Table 2 [18,19,20,22,23,24,26,27,29,30,31,32,33,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. Older age [23,24,26,29,31,55,60], higher body mass index (BMI) [19,22,23,24,26,30,31,46,47,48,49,56,57,59], reduced baseline estimated glomerular filtration rate (eGFR)/chronic kidney disease (CKD) [31,54,55,57,60], diabetes mellitus (DM) [24,26,31,34,47,55,57], nonsteroidal anti-inflammatory drug (NSAID) [23,32,53] use, and perioperative blood transfusion [23,47,53,…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other types of perioperative AKI, the pathogenesis of THA-related AKI is multifactorial including intraoperative hypotension, perioperative anemia and blood transfusion, antibiotic-related AKI, and nephrotoxic agents such as NSAID use [18,19,20,22,23,24,26,27,29,30,31,32,33,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. Our study demonstrated an overall low incidence of AKI following THA of 6.3%, and comparatively much lower than AKI incidence following other types of major surgeries such as coronary artery bypass grafting (AKI incidence approximately 20%) [63,64], vascular surgery (AKI incidence approximately 25%) [35,65], or heart valve replacement surgery (AKI incidence approximately 35% to 47%) [66].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst other studies have examined potential risk factors for AKI in orthopaedic patients [7][8][9], there is limited evidence to guide targeted intervention strategies to reduce AKI risk. Identification of patients at high risk of AKI is particularly important in a financially constrained heath system such as the NHS, where the significant increased cost associated with AKI has negative implications for population health and economics.…”
Section: Introductionmentioning
confidence: 99%
“…AKI patients stayed an additional two days in hospital compared to non AKI patients (12.0 (3.7–20.3) days for AKI vs. 9.8 (1.9–17.7) days for non AKI patients), consistent with previous findings 47 . Patients that develop AKI following elective total joint arthroplasty also have increased hospital stay 48 . The management of patients with AKI is a significant burden to the healthcare service 49 .…”
Section: Discussionmentioning
confidence: 99%